2011
DOI: 10.4172/1948-5956.s17-009
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma is the fifth most common cancer in the world. The aim of this study was to identify the possible risk factors causing HCC. Certain metabolic diseases like hepatitis B, Hepatitis C infection lead to liver cancer without causing liver cirrhosis and increases risk of HCC by 27 fold. Cirrhosis itself is an independent risk factor of inducing HCC by 5-fold. Drugs used for the treatment of diabetes have shown to cause HCC. Certain toxins like aflatoxins increase the risk of liver cancer. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…A good percentage of alcoholics were known to develop cirrhosis, which in turn developed into liver cancer. Alcohol has cocarcinogenic properties in the pathogenesis of liver cancer, and it can influence on P450 mixed function oxidase system, thus causing enhanced activation of chemical carcinogens [49,50]. A study conducted in South Africa by Mandishona E, et al among black Africans revealed that the dietary iron overload may elevate the risk of liver cancer.…”
Section: Dietary Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…A good percentage of alcoholics were known to develop cirrhosis, which in turn developed into liver cancer. Alcohol has cocarcinogenic properties in the pathogenesis of liver cancer, and it can influence on P450 mixed function oxidase system, thus causing enhanced activation of chemical carcinogens [49,50]. A study conducted in South Africa by Mandishona E, et al among black Africans revealed that the dietary iron overload may elevate the risk of liver cancer.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…The other risk factors include cirrhosis of the liver, diabetes mellitus, aflatoxin ingestion, occupational exposure to thorium dioxide or vinyl chloride, use of steroids, smoking, older age, exposure to arsenic, gender, race, obesity, and use of oral contraceptives [49,51,53].…”
Section: Non-dietary Factorsmentioning
confidence: 99%
See 3 more Smart Citations